A GUI based teaching and learning software for system sizing of a stand alone hybrid solar electricity system - Sulaiman, Marizan; Mohamad Nor, Ahmad Fateh; Omar, Rosli (nil, 2015)
This research focuses on the development of Graphical User Interface (GUI) based software that can be used to size a stand-alone hybrid solar system for teaching and learning application. The software is able to calculate the load requirements and then determine the suitable size of the stand-alone solar system’s components such as inverter, PV array, solar charge controller, and battery-bank so that the system is able to produce sufficient energy to meet the load requirements. Sizing is very important because if the solar system is not being sized carefully, it might result in producing more energy or less energy than is needed. Diesel generator is chosen to be combined with the solar system to form a hybrid solar system. GUI is used to present all of the procedures system sizing procedures to make it much easier to understand by the users. The GUI will be done by using Visual Basic 2010. The software is targeted for engineering students and practicing engineers.